2023
DOI: 10.1002/ente.202201434
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production, Purification, Storage, Transportation, and Their Applications: A Review

Abstract: The world is looking for clean and green energy as substitution for fossil fuels to minimize the greenhouse effect and climate changes threatening our existence. Solar energy, wind energy, and hydrogen gas‐based energy are few examples of promising sources of energy alternatives to fossil fuels. Hydrogen gas‐based energy is in focus today due to its availability in plenty of combined forms such as water, hydrocarbons, natural gases, etc. However, its storage and transportation are major challenges due to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 117 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…The global energy crisis caused by increasing energy consumption calls for sustainable alternative energy sources. Although H 2 is the most promising energy source with high energy density and CO 2 -free emissions, more than 90% of H 2 is produced by the steam reforming process of natural gas using fossil fuel hydrocarbons, which emit CO 2 [73]. The produced H 2 is expected to be used as energy in fuel cell vehicles (FCVs), FC buses, and power generation; however, to date it has been used in large-scale processes in various industries, including petrochemicals, electronics, metallurgy, steelmaking, pharmaceuticals, and the production of raw material chemicals.…”
Section: Co2 Capture and H2 Purificationmentioning
confidence: 99%
“…The global energy crisis caused by increasing energy consumption calls for sustainable alternative energy sources. Although H 2 is the most promising energy source with high energy density and CO 2 -free emissions, more than 90% of H 2 is produced by the steam reforming process of natural gas using fossil fuel hydrocarbons, which emit CO 2 [73]. The produced H 2 is expected to be used as energy in fuel cell vehicles (FCVs), FC buses, and power generation; however, to date it has been used in large-scale processes in various industries, including petrochemicals, electronics, metallurgy, steelmaking, pharmaceuticals, and the production of raw material chemicals.…”
Section: Co2 Capture and H2 Purificationmentioning
confidence: 99%
“…Additionally, another study focused on improving the efficiency and performance of refueling stations for Hydrogen [19]. Notably, one study achieved a cumulative hydrogen production rate surpassing the maximum reported for pure TiO2-based photocatalysts [20]. However, it's worth considering that solar energy may face limitations in meeting production requirements due to its availability primarily during the daytime, challenges related to shadows, and temperature variations.…”
Section: Hydrogen Generation From Solar Energymentioning
confidence: 99%
“…1,2 However, H 2 is highly compressible, explosive, and volatile, posting challenges for large-scale surface storage techniques. 3,4 Alternatively, subsurface formations, e.g., salt deposits, aquifers, and depleted hydrocarbon reservoirs, show great promise for large-scale hydrogen storage. 5−7 The wettability of the porous formations is vital in ensuring storage safety, efficiency, and capacity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrogen (H 2 ) is a clean and promising energy carrier to balance the mismatch between renewable energy demand and supply. , However, H 2 is highly compressible, explosive, and volatile, posting challenges for large-scale surface storage techniques. , Alternatively, subsurface formations, e.g., salt deposits, aquifers, and depleted hydrocarbon reservoirs, show great promise for large-scale hydrogen storage. The wettability of the porous formations is vital in ensuring storage safety, efficiency, and capacity. For instance, the wettability of sediment rocks is decisive in fluid transport behavior and fluid distribution.…”
Section: Introductionmentioning
confidence: 99%